The crowdsourced panopticon conformity and control on social media - Weissman, Jeremy
aBehind the omnipresent screens of our laptops and smartphones, a digitally networked public has quickly grown larger than the population of any nation on Earth. On the flipside, in front of the ubiquitous recording devices that saturate our lives, individuals are hyper-exposed through a worldwide online broadcast that encourages the public to watch, judge, rate, and rank people's lives. The interplay of these two forces - the invisibility of the anonymous crowd and the exposure of the individual before that crowd - is a central focus of this book. Informed by critiques of conformity and mass media by some of the greatest philosophers of the past two centuries, as well as by a wide range of historical and empirical studies, Weissman helps shed light on what may happen when our lives are increasingly broadcast online for everyone all the time, to be judged by the global community. --Provided by publisher.
gPart I Conformity. The human animal in civilized society Social media as an escape from freedom Meaninglessness in the present age -- Part II Control. The spectacular power of the public P2P surveillance The net of normalization -- Part III Resistance. Freedom from the public eye Strategies of resistance.
ENO Dizon (Recommending faculty) AY2022-2023
Includes bibliographical references (pages 159-170) and index.
Keywords: Social media -- Philosophy; Social media -- Moral and ethical aspects; Self-presentation.; Social media